Creative workflow analysis in event design: a case study of Innovative Creation Ltd. - Chowdhury, Afnan Mahmud (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.